Aerobic exercise combination intervention to improve physical performance among the elderly: a systematic review - Bai, Xiaorong; Soh, Kim Geok; Omar Dev, Roxana Dev; Talib, Othman; Xiao, Wensheng; Soh, Kim Lam; Ong, Swee Leong; Zhao, Chenyang; Galeru, Ovidiu; Casaru, Catalina (Frontiers Media, 2021)
The benefits of aerobic exercise for the elderly are well-known. They extend beyond cardiovascular changes and can reduce the inactivity-induced loss of strength, mobility, balance, and endurance that are vital for the safe performance of daily activities in older adults. However, the benefits of combined aerobic exercise with other exercises such as strength/resistance, multi-component and aerobic exercise remain unknown. The purpose of this study is to examine the effects of combined aerobic exercise on physical performance among the elderly, as opposed to single aerobic exercise. We searched four databases of SCOPUS, PubMed, EBSCOhost, and CINAHL Plus to find 18 articles that met criteria. Data was extracted using PICOs extraction tool and summarized using a narrative synthesis approach. Studies have shown that aerobics combined resistance/strength training (CEX), multi-component training (ME), and dance combined training has positive and significant effects on the physical performance (upper body strength and lower body strength, dynamic balance, fall risk, mobility, gait, agility, flexibility) of the elderly. CEX had additional benefits compared to aerobic training (AER) and resistance/strength training (RES) in gait speed, lower limb strength, and trunk fat. Furthermore, CEX was more effective than AER in improving sitting and stretching, elbow flexion, knee flexion, shoulder flexion and stretching, strength and body fat, function reach test, 30-s chair standing test and 6-min walking test, self-evaluation of body function. Therefore, the combination of multiple components contributes to the overall improvement in physical fitness of the elderly, thus preventing them from losing balance and reducing susceptibility to injury.